2019
DOI: 10.1097/cm9.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interleukin 10 polymorphisms on interleukin 10 production and visceral hypersensitivity in Chinese patients with diarrhea-predominant irritable bowel syndrome

Abstract: Background: Irritable bowel syndrome (IBS), a functional gastrointestinal disorder, is characterized by cytokine imbalance. Previously, decreased plasma interleukin 10 (IL-10) level was reported in patients with IBS, which may be due to genetic polymorphisms. However, there are no reports correlating the IL-10 polymorphisms with IL-10 production in patients with IBS. This study aimed to analyze the effect of IL-10 polymorphisms on IL-10 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Abnormal levels of cytokines, including TNF-α, IL-8, and IL-10, are significantly associated with IBS and bipolar disorder symptoms, indicating that IBS and bipolar disorder share similar pathophysiological mechanisms ( 75 79 ). Thus, the comorbidity of both disorders was hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal levels of cytokines, including TNF-α, IL-8, and IL-10, are significantly associated with IBS and bipolar disorder symptoms, indicating that IBS and bipolar disorder share similar pathophysiological mechanisms ( 75 79 ). Thus, the comorbidity of both disorders was hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed the influence of genetic SNPs on the development of IBS and the formation of ADPC concomitant with IBS, which is in concordance with the data of other researchers. 16 , 22 , 24 , 25 The investigated genetic SNP often had a combined effect on the diseases, affecting both the emergence of IBS and adenomatous polyps concomitant with IBS. The pronounced influence of polymorphic variations on the development of the diseases responsible for the functioning of pro-inflammatory and anti-inflammatory cytokines, reparative properties of the CM, and stability of the intestinal microbiome has been noted, which is in concordance with the findings of other authors.…”
Section: Discussionmentioning
confidence: 99%
“… 12 - 14 It is reported that SNPs are responsible for the functioning of cytokines in the human body and have the most significant impact on the development of ADPC and IBS. Interleukin (IL)-1β (rs1143627, rs 16944), 4 , 11 Interleukin IL6 (rs1800795), 13 - 16 Interleukin IL10 (rs1800872, rs1800871, rs1800896) 12 , 13 , 15 , 16 are distinguished among the SNPs, which could potentially have an impact on the disease considering their influence on dysbiosis and on changes in the colon epithelium that is caused by deviation of gene expression.…”
Section: Introductionmentioning
confidence: 99%